Penguatan Nilai-Nilai Kemuhammadiyahan Melalui Kegiatan Baca Tulis Al-Qur’an di Desa Ngadirejo: Strengthening Muhammadiyah Values Through Al-Qur'an Reading and Writing Activities in Ngadirejo Village - Dwi Rahmawati (LITERA: Jurnal Ilmiah Mutidisiplin, 2025)
The Al-Qur’an Reading and Writing (BTQ) program in Ngadirejo Village is not merely a routine religious activity, but a strategic tool for instilling core Muhammadiyah values within the local community. Using a qualitative descriptive approach, this study explores how BTQ activities organized by Muhammadiyah cadres and community members contribute significantly to the reinforcement of modern Islamic movement ideologies. The key values promoted include monotheism (tauhid), discipline, social responsibility, and a spirit of enlightening dakwah. These BTQ activities, particularly in local Qur’anic education centers (TPA) and weekly Islamic studies, have cultivated a culture of cooperation, regular worship practices, and internalization of Islamic ethics among children and parents alike. Supported by an inclusive social environment and the active role of PRA/PRM Ngadirejo, BTQ has proven to be an effective medium for ideological cadre formation at the grassroots level. This paper recommends replicating and expanding such initiatives on a broader scale with structured and sustainable methods.